Recursive Equilibrium in Stochastic Overlapping-Generations Economies - Citanna, Alessandro; Siconolfi, Paolo (Econometrica, 2010)
We prove the generic existence of a recursive equilibrium for overlapping-generations economies with uncertainty. “Generic” here means in a residual set of utilities and endowments. The result holds provided there is a sufficient number of potentially different individuals within each cohort.